A fatigue crack propagation model with resistance curve effects for an epoxy/copper interface. (July 2017) - Samet, David; Trilochan Rambhatla, V.N.N.; Kwatra, Abhishek; Sitaraman, Suresh K.
Highlights: Interfacial adhesion energy is determined by double cantilever beam tests with compliance methods. Multiple analytical models for adhesion energy are investigated and compared to FEA results. R-curve corrected Paris' Laws are determined for fatigue crack propagation tests. Abstract: Fatigue crack propagation for copper/epoxy molding compound interfaces is modeled in this work by conducting cyclic loading on double cantilever beam test specimens. The continued increase in mechanical compliance of test specimens as the crack propagates through hundreds of cycles is used to determine the crack length and thus, the crack growth rate per cycle which is used to determine the Paris' law constants as a function of strain energy release rate range. When monotonic debonding testing is conducted, it is seen that the critical strain energy release rate initially increases with the crack length and then stabilizes demonstrating the increasing resistance for the epoxy/copper interface. When such an increasing R-curve is used to normalize the strain energy release rate range, it is observed that the Paris' law constants can be determined with good consistency for a wide range of specimens over different crack lengths.